DETERMINANTS OF TEACHER PERFORMANCE AND EDUCATIONAL QUALITY IN MADRASAH IBTIDAIYAH: A PLS-SEM ANALYSIS - Muhammad Amin Jakfar Rohman; Baitur Rahman; Zainal Abidin; Yuldashev Azim Abdurakhmonovich; M. Holil (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study investigates the structural determinants of teacher performance and educational quality within Islamic elementary schools (Madrasah Ibtidaiyah) in Surabaya, Indonesia. It specifically examines the impact of principal managerial skills, charismatic leadership, and organizational culture on these outcomes. Adopting a quantitative approach, data were collected from 150 respondents, comprising teachers and principals selected through purposive sampling. The study utilized Partial Least Square Structural Equation Modeling (PLS-SEM) to test the hypothesized relationships and evaluate the predictive power of the model. The results reveal that principal managerial skills (beta=0.45) have the strongest direct influence on teacher performance, followed by organizational culture (beta=0.42 Primary School) and charismatic leadership (beta=0.38). Furthermore, teacher performance serves as a critical mediator, significantly impacting educational quality (beta=0.52). The model explains 63% of the variance in teacher performance (R2=0.63) and 58% in educational quality (R2=0.58). The findings suggest that enhancing educational quality in Islamic institutions requires a synergistic approach. Administrators should prioritize professional managerial training and foster a collaborative, value-based organizational culture to optimize teacher engagement and student outcomes. This research bridges a gap in educational management literature by applying PLS-SEM to model the simultaneous interactions between leadership styles, cultural values, and performance metrics specifically within the context of Islamic education.